Multislot Antenna with a Screening Backplane for UWB WBAN Applications. (24th October 2012) - Wei, Yun-fei; Roblin, Christophe
Abstract : A novel multislot antenna with a conducting backplane reflector (MSA-BP) designed for ultrawideband wireless body area networks (WBANs) applications is presented. The objective is to achieve a desensitization of the antenna behavior regarding the proximity effects of the human body, thanks to the field screening operated by the backplane. Partly because of the latter, the antenna is fed with a tapered CPW. The influence of antenna parameters and human body proximity on the radiation characteristics of the MSA-BP is analyzed. Simulated results of the antenna close to a three-layer arm phantom are presented. Impedance and radiation measurements of the isolated antenna as well as propagation characteristics along the human body demonstrating the desensitization effect are also presented. The characteristics of the MSA-BP, in terms of the on-body total radiation efficiency, are significantly improved compared to any (quasi-) omnidirectional counterpart.